2009
DOI: 10.1101/gad.1784909
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of mitochondrial disease as modeled in the mouse

Abstract: It is now clear that mitochondrial defects are associated with a plethora of clinical phenotypes in man and mouse. This is the result of the mitochondria's central role in energy production, reactive oxygen species (ROS) biology, and apoptosis, and because the mitochondrial genome consists of roughly 1500 genes distributed across the maternal mitochondrial DNA (mtDNA) and the Mendelian nuclear DNA (nDNA). While numerous pathogenic mutations in both mtDNA and nDNA mitochondrial genes have been identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
151
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 216 publications
3
151
0
1
Order By: Relevance
“…28,29 Inoue et al 30 reported that large-scale mtDNA depletion in hematopoietic cells leads to failure in erythropoiesis and resultant macrocytic anemia, indicating that erythrocyte differentiation is susceptible to mitochondrial respiration defects. Further, Chen et al 31 reported that mtDNA polymerase γ (POLG) mutant mice developed a progressive and ultimately fatal megaloblastic anemia that was associated with both erythrodysplasia and impaired lymphopoiesis, similar to the phenotype of our Ant2-depleted mice.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Inoue et al 30 reported that large-scale mtDNA depletion in hematopoietic cells leads to failure in erythropoiesis and resultant macrocytic anemia, indicating that erythrocyte differentiation is susceptible to mitochondrial respiration defects. Further, Chen et al 31 reported that mtDNA polymerase γ (POLG) mutant mice developed a progressive and ultimately fatal megaloblastic anemia that was associated with both erythrodysplasia and impaired lymphopoiesis, similar to the phenotype of our Ant2-depleted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction, whether it is attributable to deleterious mutations in nuclear or mtDNA genes (DiMauro and Hirano 2009;Wallace and Fan 2009) or to secondary systemic changes caused by factors such as aging/senescence, significantly impairs cell function and can result in a spectrum of pathologies. In certain circumstances, such as aging, the mechanisms for why or how mitochondrial function and dynamics become abnormal are unknown (Petersen et al 2003;Reznick et al 2007).…”
Section: Therapeutic Potential Of Signaling Pathways For the Attenuatmentioning
confidence: 99%
“…Mitochondrial transcription factor A (TFAM) is encoded by nuclear DNA and regulates mitochondrial biogenesis and mitochondrial DNA (mtDNA) transcription [1,28]. The mitochondrial genome encodes some mETC complex subunits, such as ND1-6 and ND4L of complex I, Cyt b of complex III, COX I-III of complex IV, and ATPase 6 and 8 of complex V, along with mitochondrial rRNA and tRNA [29]. We first investigated whether TFAM was induced and found that it was increasingly induced during muscle differentiation ( Figure 5A).…”
Section: Mitochondrial Alterations During Muscle Differentiationmentioning
confidence: 99%